Job burnout and its influencing factors among village doctors during the COVID-19 pandemic: a cross-sectional study - Zhao, Zixuan; Li, Qiusha; Yang, Chunxiao; Zhang, Zhongzheng; Chen, Zhongming; Yin, Wenqiang (Frontiers in Public Health, 2024)
The aim of this study is to understand the job burnout of village doctors during the COVID-19 epidemic and its influencing factors, and to provide a reference for effectively alleviating the job burnout of village doctors.A cross-sectional survey was conducted among village doctors in S province in December 2021. The survey included a general information questionnaire and the CMBI Burnout Scale. Epidata was used for dual input, and descriptive analysis, t-test, chi-square test and binary Logistic regression for statistical analysis were used.Results: A total of 993 village doctors participated in the survey. Most of them were male village doctors (62.84%), with an average age of 46.57 (SD = 7.50).Village doctors believed that the impact of the epidemic on work was serious, with a score of 3.87 ± 0.91. The economic support was small, with a score of 2.31 ± 0.99. The development space was low, with a score of 2.62 ± 0.98. The overall incidence of burnout was 53.47%. In the burnout group, 54.05% were mild, 33.14% were moderate, and 12.81% were severe. The high degree of difficulty in using WeChat (OR=1.436, 95%CI: 1.229-1.679), high work pressure (OR=1.857, 95%CI: 1.409-2.449), high risk of practice (OR = 1.138, 95%CI: 1.004-1.289), less economic support (OR=0.825, 95%CI: 0.684-0.995), less technical support (OR = 0.696, 95%CI: 0.565-0.858), and poor emotional support (OR = 0.632, 95%C1: 0.513-0.780) were more likely to have job burnout.Burnout is a common phenomenon among village doctors during the COVID-19 pandemic, which needs to be prevented and alleviated by various measures.